Analysis of errors in the writing of content in dissertations and their impact on the learning of foreign languages: A case study in Ghana - Fenyi, Daniel Arkoh; Morrison, Richard (SAINTIS Publishing, 2023)
The average postgraduate student in Ghana has about 20 years exposure in English language, having been taught and instructed in English from primary to tertiary level. It is, therefore, not far-fetched to expect the postgraduate student to commit minimal to no errors in their L2 writings. The seeming consequential minimal scholarly attention on errors in postgraduate writings regardless of the many studies on students’ errors is therefore not surprising. This study is an attempt to identify, categorise and describe the errors in postgraduate dissertations in Ghana and highlight its implications for language teaching. This exploratory qualitative study carries out a content analysis of 20 randomly selected MA, MPhil and PhD dissertations published between 2020 and 2021. The data are analysed using the theory of Error Analysis. After critically assessing the dissertations, seven (7) categories of concord errors were identified and recorded. These are; subject-verb concord errors, inverted subject concord errors, concord errors associated with ‘has’ and ‘have’, determiner-noun errors, concord errors on numbers, noun-pronoun antecedent errors and compound subject concord errors. This implies that postgraduate students are prone to errors, hence, the need to introduce or intensify the teaching of English at the postgraduate level.